2020
DOI: 10.1186/s12960-020-00534-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of breaches of the psychological contract on the job satisfaction and wellbeing of doctors in Ireland: a quantitative study

Abstract: Background Medicine is one of the most popular college degrees at both undergraduate and postgraduate level. Despite this, morale and wellbeing in doctors at all levels internationally is reportedly low. Long hours and stressful working environments have been implicated as the cause of this. The psychological contract is the implicit expectations and mutual obligations held between an employee and employer. Breaches in this contract can lead to strong negative emotional responses. This study wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…A study by Collins, et al . [ 27 ] ascertained that training and career development were the most important areas of the psychological contract for nonconsultant doctors and training and organizational support were the most important breaches. In a recent study to assess the use of e-health and job satisfaction, physicians who used digital health technology were 14.2 percentage points (95% CI, −1.3 to 29.7) and 20.3 percentage points (95% CI, 2.4 to 38.1) more likely to report, respectively, higher job satisfaction and good work–life balance, compared with the physicians who did not use it.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Collins, et al . [ 27 ] ascertained that training and career development were the most important areas of the psychological contract for nonconsultant doctors and training and organizational support were the most important breaches. In a recent study to assess the use of e-health and job satisfaction, physicians who used digital health technology were 14.2 percentage points (95% CI, −1.3 to 29.7) and 20.3 percentage points (95% CI, 2.4 to 38.1) more likely to report, respectively, higher job satisfaction and good work–life balance, compared with the physicians who did not use it.…”
Section: Discussionmentioning
confidence: 99%
“…The specialized literature on job satisfaction reveals that it is an integral part of any industry or work environment. In the case of health workers, it was found that ethical leadership positively and significantly influences job satisfaction, by: applying ethical principles to problem-solving and equity [ 24 ]; offering training and organizational support [ 25 ] together with management support and resources, despite tendencies to quit the job [ 26 ]; offering psychological support despite difficult working conditions [ 27 ]; prompting risk prevention plans [ 28 ]; offering improved health maintenance programs [ 29 ]. In all the previously mentioned sources, well-being was either positively or negatively affected by management decisions.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies were found on the correlation between wellbeing and the psychological contract ( Bester, 2019 ; Duran et al, 2019 ; Collins and Beauregard, 2020 ), as well as wellbeing and employability ( Coetzee and Engelbrecht, 2019 ), job satisfaction ( Engelbrecht, 2019 ), organizational commitment ( McInerney et al, 2015 ; Ferreira, 2019 ) and adaptability ( Ferreira, 2019 ). However, to date, no research has been found on the influence of career wellbeing on the value-oriented psychological contract in the digital era.…”
Section: Literature Reviewmentioning
confidence: 99%